2012
DOI: 10.1371/journal.pntd.0001521
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Non-Monetary Burden of Neurocysticercosis in Mexico

Abstract: BackgroundNeurocysticercosis (NCC) is a major public health problem in many developing countries where health education, sanitation, and meat inspection infrastructure are insufficient. The condition occurs when humans ingest eggs of the pork tapeworm Taenia solium, which then develop into larvae in the central nervous system. Although NCC is endemic in many areas of the world and is associated with considerable socio-economic losses, the burden of NCC remains largely unknown. This study provides the first est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 22 publications
1
75
1
1
Order By: Relevance
“…However this may be an over estimate as it is somewhat higher than the estimate for the burden of epilepsy (2.45 DALYs per 1000 person years ) in the Cameroon (Bhattarai et al, 2012).…”
Section: Cysticercosismentioning
confidence: 68%
See 1 more Smart Citation
“…However this may be an over estimate as it is somewhat higher than the estimate for the burden of epilepsy (2.45 DALYs per 1000 person years ) in the Cameroon (Bhattarai et al, 2012).…”
Section: Cysticercosismentioning
confidence: 68%
“…In the Eastern Cape of South Africa, the annual monetary burden of cysticercosis has been estimated at between US $ 18.6 million and US $ 34.2 million (Carabin et al, 2006). In Mexico is has been estimated that neurocysticercosis results in 0.25 DALYs per 1000 person years (Bhattarai et al, 2012). With a population of 114 million this represents about 28,500 DALYs per year due to neurocysticercosis.…”
Section: Cysticercosismentioning
confidence: 99%
“…In addition to neurological symptoms, neurocysticercosis can contribute to childhood learning disabilities, functional loss from resultant motor weakness, sensory deficits or chronic pain, early onset dementia, neuropsychiatric manifestations, and social stigmatization, thereby leading to reduced human productivity and economic losses. [22][23][24][25][26][27][28] Several cases of accidental drowning and burns have also been linked to epileptic seizures. 29,30 However, from the perspective of disease control and eradication, taeniasis cases are of importance as they play a key role in perpetuating the T. solium life cycle.…”
Section: -21mentioning
confidence: 99%
“…In response to the WHO's effort to estimate the global burden of neurocysticercosis, four comprehensive studies have reported estimates of burdens of T. solium cysticercosis [4][5][6][7]. While three of the studies estimated the economic burden of cysticercosis, each focusing on a specific country [4,5,7], a global extensive systematic review of literature found that the frequency of neurocysticercosis in people with epilepsy was consistent across endemic countries.…”
Section: Introductionmentioning
confidence: 99%
“…While three of the studies estimated the economic burden of cysticercosis, each focusing on a specific country [4,5,7], a global extensive systematic review of literature found that the frequency of neurocysticercosis in people with epilepsy was consistent across endemic countries. The pooled estimate was 29.0% (95%CI: 22.9%-35.5%) [6].…”
Section: Introductionmentioning
confidence: 99%